2020
DOI: 10.1155/2020/4568629
|View full text |Cite
|
Sign up to set email alerts
|

The Herbal Medicine Scutellaria-Coptis Alleviates Intestinal Mucosal Barrier Damage in Diabetic Rats by Inhibiting Inflammation and Modulating the Gut Microbiota

Abstract: Recent studies have confirmed that increased intestinal permeability and gut-origin lipopolysaccharide (LPS) translocation are important causes of metabolic inflammation in type 2 diabetes (T2D), but there are no recognized therapies for targeting this pathological state. Scutellaria baicalensis and Coptis chinensis are a classic herbal pair often used to treat diabetes and various intestinal diseases, and repair of intestinal barrier damage may be at the core of their therapeutic mechanism. This study investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 51 publications
3
22
0
Order By: Relevance
“…Decreased diversity usually indicates loss of harmonious gut microbiota, with overgrowth of pathogenic bacteria and loss of beneficial bacteria. Correspondingly, we observed that bacteria enriched in the gut microbiota of the PD mice were mainly Proteobacteria, which include many potential enteropathogenic bacteria and lipopolysaccharideproducing bacteria, such as Deltaproteobacteria, Escherichia_ Shigella, and Enterobacteriaceae (Zhang et al 2020). Furthermore, several butyrate-producing bacteria, including Lachnospiraceae_NK4A136_group, Eubacterium_fissicat-ena_group, Eubacterium_coprostanoligenes_group, Ruminococcaceae_UCG-014, Eubacterium_ventriosum_ group, Eubacterium_xylanophilum_group, Eubacterium_ nodatum_group, and Intestinimonas, were decreased in the gut microbiota of the PD mice.…”
Section: Discussionmentioning
confidence: 78%
“…Decreased diversity usually indicates loss of harmonious gut microbiota, with overgrowth of pathogenic bacteria and loss of beneficial bacteria. Correspondingly, we observed that bacteria enriched in the gut microbiota of the PD mice were mainly Proteobacteria, which include many potential enteropathogenic bacteria and lipopolysaccharideproducing bacteria, such as Deltaproteobacteria, Escherichia_ Shigella, and Enterobacteriaceae (Zhang et al 2020). Furthermore, several butyrate-producing bacteria, including Lachnospiraceae_NK4A136_group, Eubacterium_fissicat-ena_group, Eubacterium_coprostanoligenes_group, Ruminococcaceae_UCG-014, Eubacterium_ventriosum_ group, Eubacterium_xylanophilum_group, Eubacterium_ nodatum_group, and Intestinimonas, were decreased in the gut microbiota of the PD mice.…”
Section: Discussionmentioning
confidence: 78%
“…Restoration of epithelial barrier function by anti-TNF therapy may reflect mucosal healing in the setting of a dampened immune system; however, pre-clinical studies have shown that TNF signaling also modulates TJ. Many studies have shown decreased levels of intestinal TJ-consisting proteins in animal models of IBD [ 40 ], obesity, and T2D [ 41 , 42 ], with increased permeability, suggesting that a leaky pathway is responsible for LGS.…”
Section: Intestinal Barriermentioning
confidence: 99%
“…Sci. 2021, 22, x 4 of 17 of IBD [40], obesity, and T2D [41,42], with increased permeability, suggesting that a leaky pathway is responsible for LGS. Epithelial cells bind each other with tight junction, adherens junction, and desmosome.…”
Section: Intestinal Barriermentioning
confidence: 99%
“…123 Furthermore, the hypoglycaemic effects of Scutellaria-Coptis were involved in regulating gut microbiota and alleviating intestinal mucosal barrier damage. 124 Scutellaria-Coptis significantly inhibited some potential enteropathogenic bacteria and LPS-producing bacteria, such as Proteobacteria, Enterobacteriaceae, Enterobacter, Escherichia-Shigella, and Enterococcus, and increased the abundances of butyrate-producing bacteria, such as Lachnospiraceae and Prevotellaceae. 124 The change of gut microbiota resulted in alleviating intestinal mucosa barrier damage by preventing the leakage of LPS and increasing the intestinal tight junction proteins claudin-1, occluding and ZO-1 in diabetic rats.…”
Section: Traditional Chinese Medicinementioning
confidence: 96%